Prosociality in pre-school age children from Santisimo Salvador School - Walter L. Arias Gallegos (2019)
In this study we suggest the need to value the relations between prosocial behavior and some personal variables like sex and age in a group of students of preschool educational level of four and five years. We worked with a sample of 92 students (59.8% male and 40.2% female) and the Questionnaire of Prosocial Behavior of Weir and Duveen. The results indicate that, perhaps the instrument has adecuate levels of validity and reliability, there are not statistical relations between age, sex and prosocial behavior, but compared means are major in older students (p <0.018).